Heat-moisture treatment and acid hydrolysis of corn starch in different sequences. (June 2017) - Xing, Jun-jie; Liu, Yi; Li, Dong; Wang, Li-jun; Adhikari, Benu
Abstract: Dual modification of corn starch was carried out by combining acid hydrolysis (AH, 6, 12, 24 h) and heat-moisture treatment (HMT, 15, 30, 60 min) in different sequences (AH-HMT and HMT-AH). X-ray diffractometry, differential scanning calorimetry, polarized light microscopy, and rheometer were used to characterize the differences in molecular structure and physicochemical properties resulting from the sequences. Both AH-HMT and HMT-AH sequences increased the metastability of the starch granules. Starch hydrolyzed by AH for 12 h and then subjected to HMT for 15 min (AH12 -HMT15 ) has onset, peak, and conclusion gelatinization temperatures that were 4.2, 3.9 and 6.4 °C higher than those of HMT15 -AH12 one, respectively. The relative crystallinity of HMT15, 30 -AH decreased as AH time increased; however, it increased in the HMT60 -AH sample. Besides, all the temperature ranges of gelatinization of AH-HMT15, 30 were higher than those of HMT15, 30 -AH, but lower in the case of AH-HMT60 when compared to HMT60 -AH. This indicates that the perfection effect became more prominent over destruction on HMT60 for AH-HMT samples. The AH-HMT sequence also resulted into lower relative crystallinity, swelling power, solubility, gelatinization enthalpy, and pasting viscosity than in those samples produced using HMT-AH sequence. Highlights: Corn starches were acid hydrolyzed and heat-moisture treated in two sequences. The sequence of dual treatments deeply affects the physicochemical properties. Acid hydrolysis after heat-moisture treatment results in more thermostable starches. Perfection and destruction do vary during different stages of dual modifications.